2005
DOI: 10.1109/jmems.2005.859090
|View full text |Cite
|
Sign up to set email alerts
|

Film transfer and bonding techniques for covering single-chip ejector array with microchannels and reservoirs

Abstract: This paper describes a novel covering technique for an MEMS ejector array that is integrated with liquid reservoirs and microchannels on a single chip. The covering technique is based on wicking of a low viscous epoxy through the gap between the ejector wafer and a plate containing a parylene film, and allows the integrated ejector array to be fully covered by the parylene film with excellent uniformity, repeatability and yield. The technique is batch-processible and is suitable to cover many microfluidic syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Thus, it is important to maintain the liquid level constant during the ejection process, if one desires a uniform droplet size throughout the whole ejection process. We recently developed a technique to cover the ejection chamber, microchannel and reservoir so that the liquid level in the ejection chamber is maintained at a constant level through surface tension and capillary force [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is important to maintain the liquid level constant during the ejection process, if one desires a uniform droplet size throughout the whole ejection process. We recently developed a technique to cover the ejection chamber, microchannel and reservoir so that the liquid level in the ejection chamber is maintained at a constant level through surface tension and capillary force [17].…”
Section: Discussionmentioning
confidence: 99%
“…Then, we need to make the SFAT capable of ejecting droplets of uniform size consistently from droplet to droplet. This will require the liquid level to be maintained at a constant level [17] throughout the whole ejection process. In this paper, the spatial accuracy of the ejector (as shown in figure 13) is not good, because of the environmental air flow and the varying liquid level during the ejection.…”
Section: Discussionmentioning
confidence: 99%
“…However, these methods cannot be used for bonding parylene with PDMS due to either ineffective bond qualities or degradation of the material. Other existing bonding methods for either materials result in poor adhesion between PDMS and parylene [31]. This lack of suitable bonding method has been a major impediment in the widespread use of both these materials in an integrated device.…”
Section: Parylene Bonding To Other Materialsmentioning
confidence: 99%
“…Over the past years, a wide variety of polymers such as epoxies [26], SU-8 [27] and polyimide [28] have been used as the intermediate adhesive layer and their bonding strength as well as bonding robustness were investigated. Satyanarayana et al [29], for instance, demonstrated the so-called 'stampand-stick' transfer bonding method for adhesive bonding of microdevices using a UV curable adhesive.…”
Section: Introductionmentioning
confidence: 99%